SOCIO-PSYCHOLOGICAL BASICS OF COMMUNICATION IN SOCIAL WORK - K. Remizova (Publishing House of the State University of Management, 2018)
The article deals with the aspects of communicative activity of a social worker from the point of view of socio-psychological approach. The importance of building a communicative space is determined by the complexity of the object of this work and the need for intensive inclusion in interpersonal communication with clients. In addition, the ways and techniques of improving the communicative competence of social workers in order to improve the quality of life of the population have been analyzed. Social and psychological health of social professionals can contribute to the harmonious development of society as a whole and its individual structures. That is why it is important to analyze the methods, methods and techniques of communication as the main tool of human interaction in all institutions of society.